Предмет: Математика,
автор: mrssapsan2
-8b-2(3b-7a),якщо а=-5; b=-3
-0,8(x-2)+0,3(4x-7)
71
Ответы
Автор ответа:
0
-8b-2(3b-7a)=-8b-6b+14a=-14b+14a=14a-14b=14(a-b) при а=-5 и в=-3
14(-5-(-3))=14(-5+3)=14*(-2)=-28
-0,8(x-2)+0,3(4x-7)=-0,8х+1,6+1,2х-2,1=1,2х-0,8х-2,1+1,6=0,4х-0,5
14(-5-(-3))=14(-5+3)=14*(-2)=-28
-0,8(x-2)+0,3(4x-7)=-0,8х+1,6+1,2х-2,1=1,2х-0,8х-2,1+1,6=0,4х-0,5
Похожие вопросы
Предмет: История,
автор: kondratovam83
Предмет: Русский язык,
автор: kitarovazarina07
Предмет: Английский язык,
автор: TheViragon
Предмет: Математика,
автор: 20121962